Short Communication: New insights into the morphology and distribution of the Philippine endemic Etlingera pilosa (Zingiberaceae) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Naive MAK, Demayo CG, Alejandro GJD. 2021. Short Communication: New insights into the morphology and distribution of the Philippine endemic Etlingera pilosa (Zingiberaceae). Biodiversitas 22: 3175-3179. Etlingera pilosa Poulsen & Docot, only known in Negros Oriental and Negros Occidental of Visayas islands, Philippines, is recorded in the island of Mindanao for the first time, thus, extending its distributional range. The species is characterized by having sericeous ligule; leaves subsessile, narrowly obovate, coriaceous, glabrous adaxially, densely pubescent abaxially; inflorescence up to 12 cm long; flowers yellow, 3.0–3.2 cm long; subglobose to obovoid, pilose, with wart like blunt spines fruit; and seeds irregularly subglobose to oblate, black, fully embedded in juicy sour-sweet white aril. This species closely resembles E. pubimarginata but differs in having densely pubescent abaxial leaf, sericeous ligule and subglobose to obovoid, pilose, with wart like blunt spines fruit. Here, we provide a detailed description, comparison with its allied species, colored photographs to aid identification, a distribution map, an IUCN conservation assessment and a taxonomic key to the Mindanao Etlingera species.
Keywords: Alpinieae; Biodiversity; Mindanao; Philippine Flora; Zingiberales